SISTEM BISNIS INTERNET UANGRECEH.COM PERSPEKTIF HUKUM ISLAM - Fauzi Rahmawati (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
In one affiliate internet business which is a much loved community service or service to connect advertisers with the person who advertise something (advertiser). One affiliate business in Indonesia is an Internet business Uangreceh. com (ODAP: Online-based Data Assignment Program). The way it works is very simple and the same as the affiliate business in general, ie connecting seseorangdengan advertiser, and is directly affiliate will earn a commission on the services. The focus of this paper is on the Implementation of the commission in the Internet Business Uangreceh.com, testimonials on the internet about Uangreceh.com and Implementation provision of guidance to members who have difficulty conducting business Uangreceh.com. The author concludes that the implementation of the commission in the Internet business Uangreceh.com happen obscurity (gharar) in granting commissions. The writing testimonials excessive and does not correspond to the real situation in the Internet business by members Uangreceh. com is not in accordance with the concept of honesty and violate Islamic law. Mentoring by other members that are not explained in advance by the Uangreceh. Com, according to Islamic law can not be justified because there is an element of uncertainty which is not in accordance with the concept of contract in Islamic law.